Transition metal doped Sb@SnO(2) nanoparticles for photochemical and electrochemical oxidation of cysteine - Kim, Yeonwoo (Sci Rep, 2018)
Transition metal-doped SnO(2) nanoparticles (TM-SnO(2)) were synthesized by applying a thermos-synthesis method, which first involved doping SnO(2) with Sb and then with transition metals (TM = Cr, Mn, Fe, or Co) of various concentrations to enhance a catalytic effect of SnO(2). The doped particles were then analyzed by using various surface analysis techniques such as transmission electron microscopy (TEM), X-ray diffraction (XRD), scanning transmission X-ray microscopy (STXM), and high-resolution photoemission spectroscopy (HRPES). We evaluated the catalytic effects of these doped particles on the oxidation of L-cysteine (Cys) in aqueous solution by taking electrochemical measurements and on the photocatalytic oxidation of Cys by using HRPES under UV illumination. Through the spectral analysis, we found that the Cr- and Mn-doped SnO(2) nanoparticles exhibit enhanced catalytic activities, which according to the various surface analyses were due to the effects of the sizes of the particles and electronegativity differences between the dopant metal and SnO(2).